OPTIMALISASI PENDAPATAN DAERAH MELALUI PEMBAYARAN PAJAK AIR PERMUKAAN PADA UPT PENGELOLAAN PENDAPATAN DAERAH PROVINSI JAWA TIMUR JEMBER - Mauliyah, Nur Ika; Maulida, Siti Lailatul; Mubarok, Alfa Syah Barra Afsil; Aprilia, Imelda (Universitas Muhammadiyah Gresik, 2024)
This community service activity is aimed at officials/high-ranking officials and the community who use and utilize water as a business. The method for implementing this activity is by conducting outreach and counseling to related companies. And this activity will be carried out on September 7-November 20 2023 at the East Java regional revenue management unit. The result of this service activity is that there are still many companies that are not compliant and do not report to the authorities that they have used water as a business because they do not know the registration procedures. By holding socialization regarding surface water tax compliance, participants can fully understand the regulations that have been established by existing laws.